Conventional dual-cure versus self-adhesive resin cements in dentin bond integrity (Journal of Applied Oral Science, 2011)
During post preparation, the root canal is exposed to the oral cavity, and endodontic treatment may fail because of coronal leakage, bacterial infection and sealing inability of the luting cement. OBJECTIVE: this study quantified the interfacial continuity produced with conventional dual-cure and self-adhesive resin cements in the cervical (C), medium (M) and apical (A) thirds of the root. MATERIAL AND METHODS: Forty single-rooted human teeth were restored using Reforpost # 01 conical glass-fiber posts and different materials (N=10 per group): group AC=Adper™ ScotchBond™ Multi-purpose Plus + AllCem; group ARC=Adper™ ScotchBond™ Multi-purpose Plus + RelyX ARC; group U100=RelyX U100; and group MXC=Maxcem Elite. After being kept in 100% humidity at 37°C for 72 hours, the samples were sectioned parallel to their longitudinal axis and positive epoxy resin replicas were made. The scanning electron micrographs of each third section of the teeth were combined using Image Analyst software and measured with AutoCAD-2002. We obtained percentage values of the interfacial continuity. RESULTS: Interfacial continuity was similar in the apical, medium and cervical thirds of the roots within the groups (Friedman test, p>0.05). Comparison of the different cements in a same root third showed that interfacial continuity was lower in MXC (C=45.5%; M=48.5%; A=47.3%) than in AC (C=85.9%, M=81.8% and A=76.0%), ARC (C=83.8%, M=82.4% and A=75.0%) and U100 (C=84.1%, M=82.4% and A=77.3%) (Kruskal-Wallis test, p